Предмет:
МатематикаАвтор:
анонимf(x)\' = (4х + 5)’ = (4х)’ + (5)’ = 4 * 1 * x(1 – 1) +0 = 4 * x0 = 3 * 1 = 4.
f(x)\' = (5х – 8)’ = (5х)’ – (8)’ = 5 * 1 * x(1 – 1) – 0 = 5 * x0 = 5 * 1 = 5.
f(x)\' = (4x5 – 5x4.)’ = (4x5)’ – (5x4)’ = 4 * 5 * x(5 – 1) – 5 * 4 * x(4 – 1) = 20 * x4 – 20 * x3 = 20x4 – 20x3 = 20x3(x – 1).
f(x)\' = (x3 – 7x2)’ = (x3)’ – (7x2)’ = 1 * 3 * x(3 – 1) – 7 * 2 * x(2 – 1) = 3 * x2 – 14 * x = 3x2 – 14x = x(3x – 14).
Автор:
lucianoДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть